Analysis of the effect of physical barrier on genetic divergence of the Caspian trout Salmo caspius in the Dalichay River of the Lar National Park-Iran using next-generation sequencing - Seyedeh Narjes Tabatabaei; Asghar Abdoli; Iraj Hashemzade Segherloo; Faraham Ahmadzadeh; Louis Bernatchez (علوم محیطی)
Introduction:  Lar National Park is the best habitat of Salmo caspius in Iran. In other habitats located in Iran, the species has been threatened by different factors including habitat destruction, pollution, sand removal from the river bed, dam construction, introduction of exotic species, over-fishing, and other human mediated changes. Dalicahy River, as one of the major habitats of S. caspius, is ecologically different from other rivers in the Lar National Park. In this study, we assessed genetic differences (applying next-generation sequencing) of S. caspius in Dalichay River and Lar Lake; considering an impassable barrier in the mouth of Dalichay River. Material and methods: in this study fin clips from fish electrofished in the river and fin clips collected via angling in the lake were used. DNA extraction was performed using salt extraction method with an additional treatment with RNAse to degrade RNA molecules. To compare fish from Dalichay River and the Lar Lake, next generation sequencing was used. Analyses including principal components analysis (PCA) and Admixture, plus calculation of genetic differentiation (Fst) were used to compare the studied populations. Results and discussion: According to the results of principal components analysis (PCA) fish from the Dalichay River and the Lake were separated clearly along the first PC (25.11% of variation). But they were overlapped along other PCs. The results of Admixture analysis showed that Dalichay and Lake fish were always represented with different admixture clusters with little contribution from one another. Additionally, the genetic differentiation between the Dalichay and the Lake was significant. The reason for this differentiation can be the existence of a physical barrier in the moth of Dalichay that blocks the path for migration from Dalichay to the Lake and vice versa. On the other hand, it is possible that the fish in Dalichay are resident and do not show any preference for migration to the Lake. The residency behavior forms in result of low density of fish and satisfaction of biological and habitat related needs of the fish and hence no need for migration. Conclusion: overall, the results of this study showed that the fish in Dalichay River and in the Lake differ in their genetic composition and were significantly differentiated from one another. In any case, high differentiation of the fish in the Dalichay River and their isolation in addition to inability of fish from the Lake and other rivers in the Lar National Park to Dalichay, necessitates revision and taking better management approaches.